Habitual dietary fibre intake influences gut microbiota response to an inulin-type fructan prebiotic: a randomised, double-blind, placebo-controlled, cross-over, human intervention study. Issue 2 (8th January 2018) - Healey, Genelle; Murphy, Rinki; Butts, Christine; Brough, Louise; Whelan, Kevin; Coad, Jane
Abstract: Dysbiotic gut microbiota have been implicated in human disease. Diet-based therapeutic strategies have been used to manipulate the gut microbiota towards a more favourable profile. However, it has been demonstrated that large inter-individual variability exists in gut microbiota response to a dietary intervention. The primary objective of this study was to investigate whether habitually low dietary fibre (LDF) v . high dietary fibre (HDF) intakes influence gut microbiota response to an inulin-type fructan prebiotic. In this randomised, double-blind, placebo-controlled, cross-over study, thirty-four healthy participants were classified as LDF or HDF consumers. Gut microbiota composition (16S rRNA bacterial gene sequencing) and SCFA concentrations were assessed following 3 weeks of daily prebiotic supplementation (Orafti ® Synergy 1; 16 g/d) or placebo (Glucidex ® 29 Premium; 16 g/d), as well as after 3 weeks of the alternative intervention, following a 3-week washout period. In the LDF group, the prebiotic intervention led to an increase in Bifidobacterium ( P =0·001). In the HDF group, the prebiotic intervention led to an increase in Bifidobacterium ( P <0·001) and Faecalibacterium ( P =0·010) and decreases in Coprococcus ( P =0·010), Dorea ( P =0·043) and Ruminococcus (Lachnospiraceae family) ( P =0·032). This study demonstrates that those with HDF intakes have a greater gut microbiota response and are therefore more likely to benefit from an inulin-type fructan prebiotic than those with LDF intakes. Future studies aiming to modulate the gut microbiota and improve host health, using an inulin-type fructan prebiotic, should take habitual dietary fibre intake into account.